False positivity of non-targeted infections in malaria rapid diagnostic tests: the case of human african trypanosomiasis. - Philippe Gillet; Dieudonné Mumba Ngoyi; Albert Lukuka; Viktor Kande; Benjamin Atua; Johan van Griensven; Jean-Jacques Muyembe; Jan Jacobs; Veerle Lejon (Public Library of Science (PLoS), 2013)
BACKGROUND: In endemic settings, diagnosis of malaria increasingly relies on the use of rapid diagnostic tests (RDTs). False positivity of such RDTs is poorly documented, although it is especially relevant in those infections that resemble malaria, such as human African trypanosomiasis (HAT). We therefore examined specificity of malaria RDT products among patients infected with Trypanosoma brucei gambiense. METHODOLOGY/PRINCIPAL FINDINGS: Blood samples of 117 HAT patients and 117 matched non-HAT controls were prospectively collected in the Democratic Republic of the Congo. Reference malaria diagnosis was based on real-time PCR. Ten commonly used malaria RDT products were assessed including three two-band and seven three-band products, targeting HRP-2, Pf-pLDH and/or pan-pLDH antigens. Rheumatoid factor was determined in PCR negative subjects. Specificity of the 10 malaria RDT products varied between 79.5 and 100% in HAT-negative controls and between 11.3 and 98.8% in HAT patients. For seven RDT products, specificity was significantly lower in HAT patients compared to controls. False positive reactions in HAT were mainly observed for pan-pLDH test lines (specificities between 13.8 and 97.5%), but also occurred frequently for the HRP-2 test line (specificities between 67.9 and 98.8%). The Pf-pLDH test line was not affected by false-positive lines in HAT patients (specificities between 97.5 and 100%). False positivity was not associated to rheumatoid factor, detected in 7.6% of controls and 1.2% of HAT patients. CONCLUSIONS/SIGNIFICANCE: Specificity of some malaria RDT products in HAT was surprisingly low, and constitutes a risk for misdiagnosis of a fatal but treatable infection. Our results show the importance to assess RDT specificity in non-targeted infections when evaluating diagnostic tests.